IMPLEMENTATION OF TAX COLLECTION TO INCREASE INDIVIDUAL INCOME TAX REVENUE - Endang Susilawati; Asep Mulyana (Department of Accounting, Faculty of Economics, Universitas Nurtanio Bandung, 2023)
This study aims to determine the implementation of tax collection to increase personal income tax revenue whether there is a big effect after billing individuals. domestic private person. Taxes have a very large role in generating domestic cash receipts in order to realize continuity and increase in national development. The method used in this research is a quantitative method with a descriptive approach and the data used is secondary data. The results of the study show that partially Billing does not have a significant effect on Individual Income Tax Receipts.